Analisis Stilistika: Eksplorasi Gaya Bahasa dan Diksi pada Tokoh Gatotkaca dalam Novel Sisi Gelap Gatotkaca Karya Pitoyo Amrih - Moh. Hadi Kusuma; Muhammad Farhan Arby; Isfirnasan Andaniya; Mohamad Afrizal (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to carry out a thorough analysis of the use of stylistic elements, particularly in terms of diction and language style, as applied by Pitoyo Amrih to shape the character of Gatotkaca in the novel Sisi Gelap Gatotkaca. The character of Gatotkaca, traditionally depicted as a flawless heroic figure, is reimagined by the author through a more humanistic and reflective linguistic approach. Using a qualitative descriptive method alongside stylistic literary criticism, this article examines how linguistic units within the text serve as rhetorical tools to reveal internal conflicts, existential burdens, and the darker aspects of the main character. The analysis process involves identifying word choices that carry a melancholic tone as well as the prominent use of figurative language, including comparisons, contrasts, and emphatic statements. The findings indicate that the use of archaic and philosophical diction, combined with sharp irony and metaphor, effectively transforms the image of Gatotkaca from merely a symbol of physical strength into a representation of human psychological fragility. This research contributes to literary criticism by highlighting how an author’s language style can alter readers' perceptions of established myths within society's culture.